2018
DOI: 10.1002/jcop.21984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unsupportive social interactions, stigma, and symptoms on patients with myalgic encephalomyelitis and chronic fatigue syndrome

Abstract: Prior research has found a heightened risk of suicide in patients with myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS). It is possible that a number of factors including stigma, unsupportive social interactions, and severe symptoms could lead to the development of depression, suicidal ideation, and heightened risk of suicide in this patient population. Prior studies have indicated that patients often report the legitimacy of their illness being questioned by family, friends, and even their ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 72 publications
(83 reference statements)
0
31
0
1
Order By: Relevance
“…In the parent study (McManimen et al, 2018), participants completed the DePaul Symptom Questionnaire (DSQ), SF-36 (Ware et al, 2000), the Unsupportive Social Interactions Inventory (USII, Ingram et al, 2001), and a battery of stigma scales (Lennon et al, 1989). The DSQ assessed symptom frequency and severity (Jason et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the parent study (McManimen et al, 2018), participants completed the DePaul Symptom Questionnaire (DSQ), SF-36 (Ware et al, 2000), the Unsupportive Social Interactions Inventory (USII, Ingram et al, 2001), and a battery of stigma scales (Lennon et al, 1989). The DSQ assessed symptom frequency and severity (Jason et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…These results highlight the importance of investigating the risk and protective factors related to suicide in chronic illness populations like ME and CFS. Our research group recently surveyed 551 patients and found that 39.5 percent endorsed SI (McManimen et al, 2018). Interestingly, 17.9 percent of this group did not meet criteria for clinical depression and reported better functioning on the Role Emotional and Mental Health subscales of the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36; Ware et al, 2000) compared to patients meeting depression criteria and those meeting depression criteria and SI.…”
mentioning
confidence: 99%
“…ME/CFS is a complex and multifactorial disease; the World Health Organisation has described ME/CFS as a neurological disorder in the International Classification of Functioning, Disability and Health since 1969 [1]. It is also highly stigmatised [2], and there is currently neither a validated biomarker nor an effective treatment. Disease manifestation can vary between affected individuals, and some routine clinical examinations and blood tests may not evidence abnormalities [3].…”
Section: Me/cfs and The Needs Of The Severely Affected Individualmentioning
confidence: 99%
“…The dynamic interplay between interpersonal relationships, perceived moral implications of low energy states, and the disease experience of chronic fatigue has been well documented in CRF (Holley, 2000;Oktay et al, 2011) as well as a number of other chronic conditions associated with fatigue (Ware, 1992;Arroll and Howard, 2013;McManimen et al, 2018). In our study we found that social factors often led participants to dismiss their experiences of fatigue, viewing exhaustion as being reflective of personal or psychological weakness instead of a biological phenomena beyond their control.…”
Section: Discussionmentioning
confidence: 54%